BIOCHAR OPTIMIZES GROWTH, YIELD AND QUALITY OF WHEAT WITH NITROGEN UPTAKE IN LOW CALCAREOUS FERTILITY SOIL TREATED WITH MINERAL NITROGEN AND ORGANIC SOURCES - Junaid Ahmad; Shazma Anwar (Policy Research Journal, 2025)
Nutrient uptake and crop quality are significantly inclined by fertilization efforts and their supplied rates. Biochar enhanced crop productivity and their nutrient uptake of wheat, however its collaboration with organic amendments and mineral fertilizers not fully explored to these amendments to understand their role for enhancing wheat productivity and nutrient uptake. Therefore, we conducted two years research study to inspect the role of biochar with organic and mineral amendments. The experiment comprised with forms of organic sources (biochar and crop residues), Organic sources (Cowpea, Parthinium hysterphorus and Eucalyptus camaldulensis) added five tons ha -1 and thrice N doses (100, 120 and 140 kg ha -1) respectively along with one control treatment in two years of field experiment. The application of 5 tons biochar of cowpea source along with 140 kg N ha -1 as mineral fertilizer positively enhanced growth, yield and nitrogen uptake i.e. 30% improvement in leaf area tiller -1 , 37% increase in leaf area index, thousand seed weight (13%) and grain yield (29%) while their N uptake by grains and straw 12.6% and 20% respectively, total N uptake 39.2% and protein 12% was improved over treatments where no any amendments done crosswise both years. Whereas the influence was more auspicious at second year (2021-22) afterward amended of biochar with organic and synthetic amendments compared with 1 st year. Therefore, for better crop growth and yield, quality and N uptake biochar of organic source as cowpea along with 140 kg N ha -1 is recommended in semi-arid calcareous soils agro-climatic condition of the study area.